Radiologically Guided Renal Artery Embolization with an Amplatzer Vascular Plug as a Rescue Therapy for Refractory Nephrotic Syndrome in AL-Amyloidosis - I. Spozio Züst; H. R. Räz; F. Burkhalter (Case Reports in Nephrology)
Nephrotic syndrome is common in immunoglobulin light-chain (AL) amyloidosis and successful therapy may pose a challenge. We report the case of a 63-year-old patient with severe nephrotic syndrome due to primary renal AL-amyloidosis with well-preserved renal function at first presentation. Therapy with high dose steroids, loop diuretics, and ACE-inhibitors did not affect his proteinuria and he was seriously disabled because of symptomatic orthostatic hypotension and anasarca. With the patient’s informed consent, medical nephrectomy was tried with nonsteroidal-anti-inflammatory drugs (NSAIDs), cyclosporine, and aminoglycosides, with significant deterioration of his renal function, but without relevant effect on his proteinuria. Despite adequate anticoagulation life threatening thrombotic and bleeding complications occurred. Total renal ablation was finally achieved using an Amplatzer vascular plug Typ IV (AVP 4) with a self-expanding Nitinol mesh design, which was placed in both main renal arteries in the same intervention. The patient became completely anuric, protein loss stopped, and serum albumin slowly rose to normal levels. The patient’s clinical condition dramatically improved and he regained his full mobility at the price of a lifelong renal replacement therapy. To our knowledge, this is the first reported usage of such a vascular occluder in the setting of refractory nephrotic syndrome with normal kidney function at the time of first presentation.